Effects of Aerobic Fitness on Aging-Related Changes of Interhemispheric Inhibition and Motor Performance - McGregor, Keith M.; Nocera, Joe R.; Sudhyadhom, Atchar; Patten, Carolynn; Manini, Todd; Kleim, Jeffrey A.; Crosson, Bruce; Butler, Andrew J. (Frontiers in Aging Neuroscience, 2013)
Physical Fitness has been long associated with maintenance and improvement of motor performance as we age. In particular, measures of psychomotor speed and motor dexterity tend to be higher in physically fit aging adults as compared to their sedentary counterparts. Using functional magnetic resonance imaging and transcranial magnetic stimulation, we explored the patterns of neural activity that may, in part, account for differences between individuals of varying physical fitness levels. In this study, we enrolled both sedentary and physically fit middle age (40-60) and younger (18-30) adults and measured upper extremity motor performance during behavioral testing. In a follow-up session, we employed TMS and fMRI to assess levels of interhemispheric communication during unimanual tasks. Results show that increased physical fitness is associated with better upper extremity motor performance on distal dexterity assessments and increased levels of interhemispheric inhibition in middle-age adults. Further, the functional correlates of changes of ipsilateral activity appears to be restricted to the aging process as younger adults of varying fitness levels do not differ in hemispheric patterns of activity or motor performance. We conclude that sedentary aging confers a loss of interhemispheric inhibition that is deleterious to some aspects of motor function, as early as midlife, but these changes can be mediated by chronic engagement in aerobic exercise.